Combining the FLT3 Inhibitor PKC412 and the Triterpenoid CDDO-Me Synergistically Induces Apoptosis in Acute Myeloid Leukemia with ITD mutation - Ahmad, Rehan (2010)
Mutations of the FLT3 receptor tyrosine kinase consisting of internal tandem duplications (ITD) have been detected in blasts from 20–30% of patients with acute myeloid leukemia (AML) and are associated with a poor prognosis. FLT3/ITD results in constitutive auto-phosphorylation of the receptor and factor-independent survival in leukemia cell lines. The C-28 methyl ester of the oleane triterpenoid (CDDO-Me) is a multifunctional molecule that induces apoptosis of human myeloid leukemia cells. Here we report that CDDO-Me blocks targeting of NFκB to the nucleus by inhibiting IKKβ-mediated phosphorylation of IκBα. Moreover, CDDO-Me blocked constitutive activation of signal transducer and activator of transcription 3 (STAT3). We report the potent and selective anti-proliferative effects of CDDO-Me on FLT3/ITD-positive myeloid leukemia cell lines and primary AML cells. The present studies demonstrate that CDDO-Me treatment results in caspase-3-mediated induction of apoptosis of FLT3/ITD expressing cells and its anti-proliferative effects are synergistic with PKC412, a FLT3-tyrosine kinase inhibitor currently in clinical trials. Taken together, our studies indicate that CDDO-Me greatly enhanced the efficacy of the FLT3 inhibitor PKC412, suggesting that combining two separate pathway inhibitors may be a viable therapeutic strategy for AML associated with a FLT3/ITD mutation.